Subclass of Bi-Univalent Functions Associated With q-Lommel Polynomials - Renu P. Pathak; Balasaheb B. Gadekar; Mallikarjun G. Shrigan (Utilitas Mathematica, 2025)
This study uses the notion of the q-differential operator associated with q-Lommel polynomials to explain new subclass of bi-univalent functions. Additionally, we determine constraints for the initial Taylor-Maclaurin coefficients and initial Fekete-Sezgö inequalities for this recently specified subclass.